ダイ50ジ ニホン ナンキョク チイキ カンソクタイ エットウ ホウコク 2009-2010 - 門倉, 昭; カドクラ, アキラ; Kadokura, Akira (2013)
P(論文) 第50次日本南極地域観測隊越冬隊(第50次越冬隊)は28名で構成され,南極地域観測第VII期4か年計画の3年次として越冬観測を実施した.2009年1月29日に第49次越冬隊から昭和基地の運営を引き継ぎ,2010年2月1日には第51次越冬隊に無事引き渡した.観測内容としては,継続的な定常観測やモニタリング研究観測のほか,分野横断的な重点プロジェクト研究観測,医学関係の一般プロジェクト研究観測,将来の大型大気レーダー計画に係わる萌芽研究観測などを行った.越冬中数多くのブリザードがあり,基地内の除雪作業に苦心した.周辺の海氷状況は安定しており,野外行動は予定どおり実施できた.越冬期間を通じて安全に留意した訓練や対策を行った.衛星回線を利用したアウトリーチ活動も積極的に行った.そのほか,極中間圏雲の初撮影,衆議院議員選挙への投票,第51次先遣隊受入れ,豪州査察団の来訪などいくつか新しいトピックもあった. The 50th Japanese Antarctic Research Expedition (JARE-50) wintering party, consisting of 28 members, has conducted the third year program of the 7th four-year plan of JARE. JARE-50 took over the management of Syowa Station from JARE-49 on January 29, 2009 and handed over it to JARE-51 on February 1, 2010. Scientific observations carried out by JARE-50 were divided into the following five categories: 1. Steady Continuous Observations; 2. Long-term Monitoring; 3. Interdisciplinary Focused Projects; 4. Specific-Purpose Project on medical research; and 5. Preparatory Research for the future planned large atmospheric radar. There were many blizzards during the wintering, which required great efforts to clear snow. Sea ice conditions were stable, and almost all the planned outdoor operations were successfully performed. Various trainings and activities for safety management were carried out throughout the wintering, along with public outreach activities using the satellite communication network. Other items of note include photographing the Polar Mesospheric Cloud, voting in the Lower House election, the early arrival of five members of JARE-51 in November, and a visit by the Australian inspection team in January. departmental bulletin paper